Pengaruh Penggunaan Zat Aditif Minyak Cengkeh Terhadap Prestasi Mesin Sepeda Motor Injeksi 4 Langkah - Paksi, Pegi Satria Eka; Sudia, Budiman; Kadir, Abd . (Teknik Mesin Universitas Halu Oleo, 2021)
At this time, fuel oil has become a basic need by the Indonesian people due to the increase in the use of vehicles, while the government is still subsidizing fuel oil. For this reason, it is necessary to save on the use of fuel oil. The alternative that can be done is reformulating fuel oil with additives that function to enrich the oxygen content in the fuel. The purpose of this study is to determine the performance of the engine which can be seen from the fuel consumption and acceleration of the vehicle in which the percentage of clove oil mixing which is most effective in its use will be known. This research includes mixing 1.5%, 2.5%, 3.5% and 4.5% mixture of clove oil to premium/gasoline. In this study, the formulation of a premium fuel/gasoline mixture with clove oil was most effective and efficient on fuel consumption, namely in the stationary test it was a mixture of 1.5% while in the running test it was a mixture of 2.5%. For the acceleration test, the best mixing formulation is in the 4.5% mixture formulation, both in the 0-70 km and 40-70 km tests.